THE RESULTS OF EXAMINATION OF MEDICAL CARE QUALITY FOR ASSOCIATED VERTEBRO-SPINAL-CORD INJURY - V. V. Shchedrenok; I. V. Yakovenko; S. V. Orlov; I. A. Simonova; P. V. Krasnoshlyk; O. V. Moguchaya (Travmatologiâ i Ortopediâ Rossii, 2016)
Medical care quality assessment for patients with vertebro-spinal-cord injury at different stages in St.-Petersburg during year was performed. The first aid in the most cases (74,8%) was rendered by emergency service. A vertebro-spinal-cord injuries were not diagnosed by a staff of line and special medical aid brigades in 31,6-51,9%. The causes of incorrect diagnostics at hospital stage: insufficient and delayed patient examination, underestimation of injury severity in consequence of delayed use of neuro-imaging methods. Surgical operations for vertebro-spinal-cord injuries were performed in 59 (8%) cases. 43 (73%) patients needed in vertebral fixation.